Effect of lipid-lowering and anti-hypertensive drugs on plasma homocysteine levels - Dierkes, Jutta (Dove Medical Press, 2007)
Elevated plasma concentrations of homocysteine, a sulfur-containing amino acid, are a risk factor for coronary, cerebral and peripheral artery disease. Next to other factors, drugs used for the prevention or treatment of cardiovascular disease may modulate plasma homocysteine levels. Thus, a drug induced homocysteine increase may counteract the desired cardioprotective effect. The aim is to summarize the current knowledge on the effect of two important classes of drugs, lipid-lowering drugs and anti-hypertensive drugs, on homocysteine metabolism. Among the lipid-lowering drugs, especially the fibric acid derivatives, which are used for treatment of hypertriglyceridemia and low HDL-cholesterol, are associated with an increase of homocysteine by 20%–50%. This increase can be reduced, but not totally avoided by the addition of folic acid, vitamin B12 and B6 to fibrates. HMG-CoA reductase inhibitors (statins) do not influence homocysteine concentrations substantially. The effects of nicotinic acid and n3-fatty acids on the homocysteine concentrations are less clear, more studies are necessary to clarify their influence on homocysteine. Antihypertensive drugs have also been studied with respect to homocysteine metabolism. A homocysteine increase has been shown after treatment with hydrochlorothiazide, a lowering was observed after treatment with ß-blockers, but no effect with ACE-inhibitors. The clinical significance of the homocysteine elevation by fibrates and thiazides is not clear. However, individual patients use these drugs for long time, indicating that even moderate increases may be important.